STUDY ON CONVENTIONAL RISK FACTORS IN ACUTE CORONARY SYNDROME - Khatri, Prabin; Simkhada, Rabindra (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Acute coronary syndrome is one of the common cardiovascular diseases. Smoking, dyslipidemia, hypertension, diabetes and obesity are conventional risk factors. Different studies have shown variable prevalence of these risk factors. This study was designed to see the prevalence of these risk factors in our setting and see their correlation with different types of acute coronary syndrome. MATERIAL AND METHOD: This was a hospital based observational study conducted at Universal College of Medical Science Teaching Hospital, Bhairahawa from September 2012 to August 2013. A total of 100 consecutive patients were enrolled after applying inclusion and exclusion criteria. RESULTS: Out of 100 study patients, 64% were male and 36% were female. Their age ranged from 30 years to 87 years with mean age of 60 ± 12.90 year. Hypertension was present in 64%, 62% were dyslipidemic. Similarly 39% were smoker and 19% had diabetes. Sex (p=0.01) and hypertension (p<.01) showed significant positive correlation with type of acute coronary syndrome. CONCLUSION: Hypertension was the most prevalent risk factor for the occurrence of acute coronary syndrome. Diabetes mellitus, smoking, and dyslipidemia was also present in considerable numbers. Gender and hypertension showed significant positive correlation with type of Acute Coronary Syndrome. Journal of Universal College of Medical Sciences (2015) Vol.3(2): 1-4